ANALYSIS OF COMPETITIVE ADVANTAGE IN IMPROVING THE QUALITY OF INDONESIAN MSME PRODUCTS TO FACE THE DOMINATION OF CHINESE IMPORTED PRODUCTS IN THE ASEAN CHINA FREE TRADE AREA (ACFTA). - Rufida Tahta (Mediasi: Journal of International Relations, 2021)
This study discusses Indonesia's strategy in helping MSMEs face the dominance of imported Chinese products in the Indonesian domestic market. Since the enactment of the ACFTA agreement, MSMEs, which are an important pillar of the Indonesian economy, have felt a significant negative impact. This is due to globalization that has changed the order in various aspects of life, especially the world economy, where countries are required to carry out free trade which includes the application of a 0 tariff policy in import exports. Due to Indonesia's lack of readiness in facing the free trade era, this caused MSMEs and domestic industries to go out of business because they were unable to compete with various imported goods originating from China. The purpose of this study is to analyze how the Indonesian government supports MSMEs in facing the dominance of imported Chinese products in Indonesia after the ACFTA cooperation. In this study, researchers discussed the increase in MSMEs in terms of product quality and quantity and the increase in human resources, which has never existed in previous research in accordance with the title that the researchers took, namely "Analysis of Indonesia's Strategy to Support the Improvement of MSME Product Quality in the Face of the Dominance of Chinese Imported Products within the scope of the ASEAN China Free Trade Area (ACFTA) with Theory Competitive Advantage". This research uses the theory of Competitive Advantage as an analytical knife in this study because the theory is in line with the focus of the research that the researchers took, namely the Indonesian government's strategy in increasing MSMEs through the quality and quantity of products and increasing human resources. This research uses qualitative methods with a descriptive approach. This research in collecting data is carried out through document analysis and meaning. The results of this study show thatsince the enactment of the ACFTA agreement, MSMEs, which are an important pillar of the Indonesian economy, have felt a significant negative impact. This is due to the implementation of the 0 tariff policy in import exports. Therefore, the government launched programs in suppressing the dominance of imported Chinese products in Indonesia such as the holding of BLK to improve the quality of human resources, the AOSD program to expand the market reach of MSMEs, Rumah BUMN as a liaison between MSMEs and partner companies, The EHP program is a program to eliminate import duty tariffs, cooperation in infrastructure development that supports the absorption of human resources, investment investment and cooperation between government institutions such as Indonesian SOEs and China Railway International Co.Ltd in the construction of high-speed trains, and the establishment of rules of origin to prevent trade deflection.